MASS, INSTANCE, ATOMS, AND THE SEVENTH HYPOTHESIS OF PLATO’S PARMENIDES - Peddle, Francis (Science et Esprit)

(untitled) (Collège universitaire dominicain, Ottawa, 2022)
The purpose of this essay is to glean some concepts out of the seventh hypothesis of Plato’s Parmenides that can provide a contribution to the often unsatisfying modern debates about the nature of atoms, mass, and what might constitute an instant. The seventh hypothesis (hereafter H7, similarly for the other hypotheses) of Part II of the Parmenides is one of the more neglected of all the hypotheses in the dialogue, despite the fact that it introduces some very novel terms and arguments. A brief overview of Part II of the dialogue is followed by a detailed analysis of the argument in H7. The conclusion brings this essay around to the relevance of H7 for contemporary reflections in theoretical physics and cosmology.